Death in the afternoon - Hemingway, Ernest, 1899-1961. (London : Vintage, 2000)
Describes all phases of bullfighting, from the raising and training of the bulls to sketches of the bullfighters themselves.
Adult
Keywords: Bullfights; Bullfights